THE INFLUENCE OF GROUP INVESTIGATION (GI) LEARNING MODEL ON GEOGRAPHY LEARNING OUTCOMES OF SMA NEGERI 1 BANJARBARU - Restu Ulfah (Journal Learning Geography, 2020)
The purpose of this study was to examine the effect of Group Investigation model of learning on learning outcomes of geography at SMAN 1 Banjarbaru academic year 2013/2014. This study was a quasi-experimental study (quasi-experiment) with a research design Non-Equivalent Control Group Design. Data were analyzed using t-test. The results of the calculation of t test analysis of data obtained p-level less than 0.05 (p 0.05) of 0.01. The results of these calculations prove that the Group Investigation model of learning effect on learning outcomesTujuan penelitian ini untuk menguji pengaruh model pembelajaran Group Investigation terhadap hasil belajar geografi pada siswa SMAN 1 Banjarbaru tahun ajaran 2013/2014. Penelitian ini merupakan penelitian eksperimen semu (quasi experiment) dengan desain penelitian Non Equivalent Control Group Design. Data yang diperoleh dianalisis menggunakan t-test. Hasil perhitungan analisis uji t diperoleh data p-level lebih kecil dari 0,05 (p0,05) yaitu 0,01. Hasil perhitungan ini membuktikan bahwa model pembelajaran Group Investigation berpengaruh terhadap hasil belajar.